Status Nutrisi Kerbau Betina di Peternakan Rakyat Cibungbulang: Pengaruh Suplementasi Indigofera sp dan Gaplek terhadap Perubahan Profil Darah - A Sudarman; N Hidayati; S Suharti (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
This study aimed to evaluate the effect of Indigofera sp and cassava flake supplementation on the nutritional status of female buffaloes fed on rice straw and field grasses in smallholder farmers in Cibungbulang, Bogor. This study used four female buffaloes of 4-10 years old and an average body weight of 428.88 ± 86.05 kg. The treatments were T0 = without supplementation and T1 = supplementation of 50% Indigofera leaf and 50% cassava flake. The variables observed were body weight gain, blood glucose, cholesterol, total protein, albumin, hematocrit and hemoglobin. Data were analyzed using Paired Samples T-test. The results showed that the nutritional status of buffaloes that were reared in semi-intensive were in normal condition. Supplementation of Indigofera sp and cassava has a positive influence on body weight gain, blood metabolite levels, hematocrit and hemoglobin of female buffaloes. Daily weight gain was obtained at 732.1 g head-1day-1. Blood glucose increased from 53.97 to 60.86 mg dL-1, albumin from 3.44 to 3.78 g dL-1, blood cholesterol from 37.43 to 50.84 mg dL-1 and hematocrit from 26.75 to 29.75%. The conclusion is that giving supplements of Indigofera sp and cassava for two weeks can improve the nutritional status of buffaloes reared traditionally. Keywords: cassava flake, hematocrit, haemoglobin, Indigofera, buffalo, blood metabolite